2021
DOI: 10.3390/w13152074
|View full text |Cite
|
Sign up to set email alerts
|

River Basin Management Planning in the Republic of Ireland: Past, Present and the Future

Abstract: The River Basin Management Plan (RBMP) is an essential component of the European Union Water Framework Directive that details an integrated approach required to protect, improve and sustainably manage water resources. RBMP were intended to be produced for the periods 2009–2015, 2016–2021 and 2022–2027. However, after two years of delays in the development processes, the Republic of Ireland produced its first RBMP in 2010. The second RBMP cycle was also implemented in 2018 and is expected to run until the end o… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 25 publications
0
7
0
Order By: Relevance
“…The readily available methods for the prioritization of hydrological units with a considerable need for the adoption of structural water retention measures as well as advanced techniques for NSWRM designs and placements [40][41][42][43][44][45] and this study support their inclusion in watershed management plans. However, to successfully introduce these steps and to employ a complex approach require a comprehensive, whole-basin survey, including SWOT and cost-benefits analyses, as well as the appropriate engagement of different stakeholders, ranging from regional policy makers and municipalities to farmers and landowners [94][95][96].…”
Section: Discussionmentioning
confidence: 99%
“…The readily available methods for the prioritization of hydrological units with a considerable need for the adoption of structural water retention measures as well as advanced techniques for NSWRM designs and placements [40][41][42][43][44][45] and this study support their inclusion in watershed management plans. However, to successfully introduce these steps and to employ a complex approach require a comprehensive, whole-basin survey, including SWOT and cost-benefits analyses, as well as the appropriate engagement of different stakeholders, ranging from regional policy makers and municipalities to farmers and landowners [94][95][96].…”
Section: Discussionmentioning
confidence: 99%
“…Even though citizens remain generally unaware of the economic and environmental impacts of urban floods, their contribution is essential to identify new adaptation strategies [20]. Antwi et al (2021) [21] examined stakeholders' perspectives of the second River Basin Management Plan for the management and governance of water resources in the Republic of Ireland. They concluded that stakeholder collaboration and awareness is necessary to achieve effective and efficient water policy measures, water quality systems, and water services network [21].…”
Section: Introductionmentioning
confidence: 99%
“…Antwi et al (2021) [21] examined stakeholders' perspectives of the second River Basin Management Plan for the management and governance of water resources in the Republic of Ireland. They concluded that stakeholder collaboration and awareness is necessary to achieve effective and efficient water policy measures, water quality systems, and water services network [21].…”
Section: Introductionmentioning
confidence: 99%
“…An innovation in sustainable river basin planning strategies and management faced uncertainties and conflicting interests among experts, while critical zones for implementing policies were identified and prioritized with improving reliability on the model results and optimistic, pessimistic and nominal viewpoints were obtained [22]. A qualitative analysis in the Republic of Ireland revealed several bodies associated with water management including local and international environmental organizations and local authorities [23].…”
Section: Introductionmentioning
confidence: 99%
“…The key policies from another study include regulation of heavy metals disposal, promoting hydropower, transformation towards organic farming, involvement of stakeholders and control of dams and barrages in a river basin in India [22]. A pressure on water resources is also made by agriculture, forestry, peat extraction, eutrophication and hydro-morphology in the Republic of Ireland [23].…”
mentioning
confidence: 99%